The Views of Health Workforce Managers on the Implementation of Workload Indicators of Staffing Need (WISN) Method in Primary (International Journal of Studies in Nursing, 2018)
Background: Several African countries, including South Africa, are using the Workload Indicators of Staffing Need (WISN) method, as the preferred health workforce planning and management approach. Ineffective implementation of this method can however mean that health outcomes are not improved. Objectives: This study explored the views of health workforce managers regarding potential barriers and enablers to implementation of the WISN method in South African primary healthcare (PHC) settings. Method: This study adopted a qualitative approach and Grounded Theory research design. Following ethics clearance, a total of fourteen participants, PHC nurse managers and WISN coordinators were purposefully selected to participate in the study. Data were collected through focus group interviews and document analysis. Open, axial and selective coding was conducted to analyse data, including the use of Nvivo data analysis software to assist with the analysis. Findings: Participants in this study highlighted a number of conditions necessary for the successful implementation of the WISN method. These included political will and leadership, provision of necessary support to enable implementation process, collaborative and consultative approach by stakeholders, clear, efficient and consistent communication, resources availability, continued support in implementing WISN and stability in leadership and staff in PHC settings. Conclusions: The study concludes that successful WISN implementation requires addressing implementation barriers, such as unavailability of financial and human resources, and enhancing enablers, such as normative guides implementation guideline, technical capacity and availability of continuous support to implementers. This study’s results can be used to enhance WISN implementation and health systems strengthening.